2011
DOI: 10.1348/000709910x522393
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self and peer perceptual differences on student social behaviour

Abstract: BACKGROUND. The development of socially appropriate behaviour is increasingly seen as an important part of a student's education. AIM. To examine whether changes in a student's behaviour, as part of an ongoing social empathy intervention, can in part be explained by the difference between the student's self-perception of their behaviour and their peers-perception of their behaviour. METHOD. A school population (383 students from year levels 4 to 6) was assessed for a range of prosocial and antisocial behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…This process can function directly on the student in this way, or it may be more indirect if classmates observe the distinctive feedback rendered to playful boys by the teacher. Mirroring the teacher, their classmates may treat them differently as well, and the playful boys will respond to this influence to interpret their own behavior (Brown, 2012 ) and to guide their future actions (Armstrong, 2011 ). The finding that it was not until third grade that playful boys acutely perceived and reacted to social changes in how they were viewed by their peers may be attributable to enhanced social-cognitive and socio-emotional abilities as children move through middle childhood.…”
Section: Discussionmentioning
confidence: 99%
“…This process can function directly on the student in this way, or it may be more indirect if classmates observe the distinctive feedback rendered to playful boys by the teacher. Mirroring the teacher, their classmates may treat them differently as well, and the playful boys will respond to this influence to interpret their own behavior (Brown, 2012 ) and to guide their future actions (Armstrong, 2011 ). The finding that it was not until third grade that playful boys acutely perceived and reacted to social changes in how they were viewed by their peers may be attributable to enhanced social-cognitive and socio-emotional abilities as children move through middle childhood.…”
Section: Discussionmentioning
confidence: 99%
“…A reason may be that too little structuring, consistency, and coordination exist between the support actions chosen at the national level and the real requirements and concrete facilities at the levels of the school board, school, class, and pupil. Another reason seems to be the lack of reliable and valid assessment and implementation of specific social pedagogical characteristics in schools and the consequent assessment of longitudinal safety effects with the pupils (Armstrong, 2011). Ferraro and LaGrange (1987) and Gray, Jackson, and Farrall (2011) discuss the fear of crime research and conclude that measurement of fear of crime should be improved by giving adequate attention to conceptualization issues, tapping of emotional aspects of feelings of safety concerning specific situations, and consistent use of reliable and valid measurement procedures.…”
mentioning
confidence: 99%
“…Whether designed to help individuals cope with a serious illness or to alleviate distress in whole communities following a disaster, such services may range from mental health counselling, psycho-education, and group support to spiritual support and other assistance which is provided by psychologists, social workers, and pastoral counsellors, among others. Studies have found that student social behaviour and the availability of psycho-social support may have both positive impacts, for example, in relation to academic performance and negative impacts, such as in terms of fostering crime; substance abuse; and peer relationship problems, on students' overall well-being (Armstrong, 2011).…”
Section: Student Social Behaviour and Psycho-social Supportmentioning
confidence: 99%